GENERIC SHOPPING MALL DIRECTORY (GSMD) HYBRID MOBILE BASED APPLICATION DESIGN WITH SCRUM METHOD (CASE STUDY: GRAND BATAM MALL) - Yefta Christian; Yusuf Yusuf (Universitas Internasional Batam, 2022)
Malls are shopping centers with an assortment of more complete and better facilities due to the advancement of technology. In big cities, the mall buildings can be very large, making it difficult for people to find the store they want to visit. A reliable directory system was needed to guide people to the stores they wanted to visit. The developed mobile directory application was developed using a hybrid method that used the scrum method. A hybrid application is built using standard web technologies such as HTML, CSS, and JavaScript. To ensure the highest quality, a scrum development method is used so that the maximum value is produced. With the scrum method, a software product can be developed using stages that align with the requirements of its end users or clients. The stages taken in designing the system start from collecting data, identifying problems, analyzing user needs, designing applications, and implementing the system. As a result of the study, it was concluded that the scrum method facilitates the design and development of the application on time and precise, so that the intensive system development time efficiency will be achieved.